Penyuluhan Pengabdian Hukum dalam Mengatasi Dampak Negatif Judi Online terhadap Kesejahteraan Buruh (PUNDIMAS: Publikasi Kegiatan Abdimas, 2023)
This journal discusses the negative impact of online gambling on workers' welfare and the legal service counseling effort to mitigate its effects. Online gambling is a modern form of gambling that significantly affects individual well-being, particularly that of laborers. Online gambling addiction disrupts work performance, upsets the balance between work and personal life, and negatively affects mental and physical health. The proposed legal service counseling program aims to provide understanding of the risks and consequences of online gambling to workers. From a legal perspective, online gambling violates legal and religious norms. Prohibitions are reinforced through various regulations such as Criminal Law and Information and Electronic Transactions (ITE) Laws. Religious norms, especially in Islam, also prohibit gambling as it is considered a tool of the devil to sow discord among believers. Factors contributing to online gambling include the desire for quick wealth, easy access to online gambling platforms, economic pressures, and a lack of awareness about the risks. Negative consequences include decreased work productivity, financial disturbances, and even suicide risks. Preventive measures encompass awareness, education, social campaigns, and support and recovery for those affected. Collaborations between governments, businesses, and communities are pivotal in addressing online gambling issues.